Quality assessment of online information on Brazilian domain sites related to dental implants. - Lobato, Maria Zeneide; Martins, Ana Clara (Brazilian Journal of Implantology and Health Sciences, 2020)
Brazil is one of the biggest consumer markets for dental implants in the world, and most of the information that patients have about this therapy is acquired from the internet. However, no study evaluated the quality of online information related to dental implants in Brazilian domain sites. The aim of the study was to evaluate the quality of online information in Portuguese language related to dental implants and to compare this information with the literature in English language. The term "dental implants" was searched using Google and Yahoo!. Sites of the first 10 pages of each search engine were considered for the study, and at the end 53 sites were included. The Health-Related Web Site Evaluation Form (HRWEF/ Emory) was applied and a total score was assigned to each of the sites by two researchers. The HRWEF/Emory questionnaire gives a possible variation of 50% -100%, being below 75% considered poor, between 75 and 90% adequate and above 90% excellent. 5.66% of the sites had poor score, 84.90% adequate and 9.43% excellent, with an average of 83.18%. When the questionnaire was separated by categories of linked issues, the quality scores were lower than those observed in the overall assessment (39.52% were poor), showing that the scores on the final results were increased by the readability and navigability categories. There was no difference regarding quality of websites between the search engines Google and Yahoo!. The quality of information on Brazilian domain sites related to dental implants is overall adequate according to HRWEF/Emory. There is no difference in the quality of information between search engines Google and Yahoo!. Direct comparisons with studies evaluating the quality of information in other languages are inappropriate because of the use of different assessment tools